2017
DOI: 10.3934/cpaa.2017109
|View full text |Cite
|
Sign up to set email alerts
|

Existence and convexity of solutions of the fractional heat equation

Abstract: We prove that the initial-value problem for the fractional heat equation admits an entire solution provided that the (possibly unbounded) initial datum has a conveniently moderate growth at infinity. Under the same growth condition we also prove that the solution is unique. The result does not require any sign assumption, thus complementing the Widder’s type theorem of Barrios et al. [1] for positive solutions. Finally, we show that the fractional heat flow preserves convexity of the initial datum. Incidentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…More recently, several authors have analyzed properties such as estimates of the heat kernel, the weak Harnack inequality and the Hölder continuity of solutions, interior and at the boundary, for more general nonlocal parabolic equations, results of Fujita type, a Widder type theorem, Nash-type inequalities, eigenvalue estimates, nonlocal porous medium equation etc., see e.g. [Ko95], [BLW05], [BJ07], [BM07], [BGR10], [CKK11], [DQRV12], [FK13], [BP13], [BPSV14], [AMPP16], [BSV17], [Fr17], [GI17], [V17], [V17'] but this list is by no means exhaustive. The regularity theory for very general nonlocal parabolic operators has been developed in the paper [CCV11].…”
Section: This Givesmentioning
confidence: 99%
“…More recently, several authors have analyzed properties such as estimates of the heat kernel, the weak Harnack inequality and the Hölder continuity of solutions, interior and at the boundary, for more general nonlocal parabolic equations, results of Fujita type, a Widder type theorem, Nash-type inequalities, eigenvalue estimates, nonlocal porous medium equation etc., see e.g. [Ko95], [BLW05], [BJ07], [BM07], [BGR10], [CKK11], [DQRV12], [FK13], [BP13], [BPSV14], [AMPP16], [BSV17], [Fr17], [GI17], [V17], [V17'] but this list is by no means exhaustive. The regularity theory for very general nonlocal parabolic operators has been developed in the paper [CCV11].…”
Section: This Givesmentioning
confidence: 99%
“…It has been shown that the associated kernel K(x, t) is smooth and positive in R n × R + . See [13,25] for more details. The following estimate was given in Lemma 3.1 in [25].…”
Section: 2mentioning
confidence: 99%
“…Next we mention shortly several results devoted to equations with either fractional space operator or with fractional time derivative. Among the papers, concerning Cauchy problems for equation with the usual first derivative in time and with either fractional Laplacian or with a more general nonlocal space operator we refer to the papers [12], [14], [20], [35], [37], [47]. These papers contain, in particular, results on Schauder estimates and regularity in Hölder or Hölder -like classes.…”
mentioning
confidence: 99%